A Market Framework for Energy Bidding Decision Making Strategy to provide a Competitive Mechanism in the Context of Deregulated Electricity Market - Ahmed Mohamed, Ahmed Haidar; Lai, Carmen; Muttaqi, Kashem M. (2021)
In the modern power grid operation, the regulatory goal of the market is to provide continuous electricity supply to the customers with reasonable energy prices. The current structure of energy market in Malaysia follows the single buyer market model, where the generation is procured solely by a single utility with a limited competition, which is not effective in lowering the electricity prices. This paper proposes a market framework for competitive strategies to achieve maximum benefits of the power grid in Sarawak, Malaysia while the optimal bidding in the day-ahead market is assessed. Game theory with the non-cooperative scheme is applied for the electricity market comprising various participants. The performance of the proposed approach is evaluated using a practical power grid with data of the electricity market obtained from available sources. The feasibility of electricity market deregulation in Sarawak is proven to be effective, as the proposed framework can provide insight into the generated revenue of energy producers in a fair and competitive market environment.